Given,
"(D^2+DD'-6D'^2)z= y\\cos x" Now, Auxiliary equation will be
"m^2+m-6=0\\\\\n\\implies (m-2)(m+3)=0\\\\\n\\implies m=2,-3" Hence,
"C.F=\\phi_1(y+2x)+\\phi_2(y-3x)" Now,
"P.I=\\frac{1}{(D^2+DD'-6D'^2)}y\\cos x\\\\\n\\implies P.I=\\frac{1}{(D+3D')(D-2D')}y\\cos x\\\\\n=\\frac{1}{D+3D'}\\int_{D-2D'}y\\cos x \\, dx\\\\\n=\\frac{1}{D+3D'}[(c_1-2x)\\sin x-2\\cos x]\\\\\n=\\frac{1}{D+3D'}(y\\sin x-2\\cos x)\\\\\n=\\int_{D+3D'}y\\sin xdx-\\int_{D+3D'}2\\cos x dx\\\\\n=\\int_{D+3D'}(c_2+3x)\\sin xdx-\\int_{D+3D'}2\\cos x dx\\hspace{1cm}(y=c_2+3x)\\\\"
"\\implies P.I=-y\\cos x+\\int\\cos x \\, dx =-y\\cos x+\\sin x"
Therefore the complete solution is
"C.F+P.I=\\phi_1(y+2x)+\\phi_2(y-3x)+-y\\cos x+\\sin x"
Comments
Leave a comment